2020
DOI: 10.1111/jphp.13204
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin: a monoterpene glycoside from plants of Paeoniaceae family with diverse anticancer activities

Abstract: Objectives Paeoniflorin, a representative pinane monoterpene glycoside in plants of Paeoniaceae family, possesses promising anticancer activities on diverse tumours. This paper summarized the advance of Paeoniflorin on cancers in vivo and in vitro, discussed the related molecular mechanisms, as well as suggested some perspectives of the future investigations. Key findings Anticancer activities of paeoniflorin have been comprehensively investigated, including liver cancer, gastric cancer, breast cancer, lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 78 publications
(151 reference statements)
1
34
0
Order By: Relevance
“…Paeoniae radix is the root of Paeonia lactiflora, a herbaceous perennial plant belonging to the family Paeoniaceae (27). Paeoniflorin, a monoterpene glycoside, is one of the major active components of Paeoniae radix.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniae radix is the root of Paeonia lactiflora, a herbaceous perennial plant belonging to the family Paeoniaceae (27). Paeoniflorin, a monoterpene glycoside, is one of the major active components of Paeoniae radix.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin is a monoterpene glycoside with various anti-cancer activities and is derived from Paeonia lactiflora . Studies have shown that paeoniflorin has broad-spectrum anti-tumor activities against various cancers ( 76 ), including those of liver ( 77 ), lungs ( 78 ), breast ( 79 ), and pancreas ( 80 ). miR-124 levels are significantly increased in paeoniflorin-treated MGC-803 cells, which inhibits PI3K/Akt and p-STAT3 expression.…”
Section: Active Ingredients Of Chinese Medicine Targeting Mirna Inhibmentioning
confidence: 99%
“…Growing evidence indicates the potential of natural compounds to serve as successful anticancer agents [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%